An overview of metal-free synthetic routes to isoxazoles: the privileged scaffold. Issue 52 (6th October 2021) - Das, Soumyadip; Chanda, Kaushik
Abstract : Isoxazole, a five-membered heterocyclic moiety commonly found in many commercially available drugs. This review article presents a comprehensive overview on metal-free synthetic routes for the synthesis of isoxazoles with significant bioactivities. Abstract : In the field of drug discovery, isoxazole is a five-membered heterocyclic moiety commonly found in many commercially available drugs. In view of their enormous significance, it is always imperative to unleash new eco-friendly synthetic strategies. Among various novel synthetic techniques in use for isoxazole synthesis, most synthetic methods employ Cu(i ) or Ru(ii ) as catalysts for (3 + 2) cycloaddition reaction. The particular disadvantages associated with metal-catalyzed reactions are high costs, low abundance, toxicity, a significant generation of waste, and difficulty to separate from the reaction mixtures. In view of these drawbacks, it is always imperative to develop alternate metal-free synthetic routes. This review article highlights a comprehensive overview on the potential application of metal-free synthetic routes for the synthesis of isoxazoles with significant biological interests.